Whole Blood for Resuscitation in Adult Civilian Trauma in 2017: A Narrative Review. (July 2018) - Pivalizza, Evan G.; Stephens, Christopher T.; Sridhar, Srikanth; Gumbert, Sam D.; Rossmann, Susan; Bertholf, Marsha F.; Bai, Yu; Cotton, Bryan A.
Abstract : After a hiatus of several decades, the concept of cold whole blood (WB) is being reintroduced into acute clinical trauma care in the United States. Initial implementation experience and data grew from military medical applications, followed by more recent development and data acquisition in civilian institutions. Anesthesiologists, especially those who work in acute trauma facilities, are likely to be presented with patients either receiving WB from the emergency department or may have WB as a therapeutic option in massive transfusion situations. In this focused review, we briefly discuss the historical concept of WB and describe the characteristics of WB, including storage, blood group compatibility, and theoretical hemolytic risks. We summarize relevant recent retrospective military and preliminary civilian efficacy as well as safety data related to WB transfusion, and describe our experience with the initial implementation of WB transfusion at our level 1 trauma hospital. Suggestions and collective published experience from other centers as well as ours may be useful to those investigating such a program. The role of WB as a significant therapeutic option in civilian trauma awaits further prospective validation.